Mice lacking PGC-1β in adipose tissues reveal a dissociation between mitochondrial dysfunction and insulin resistance - Enguix, Natàlia (Elsevier, 2013)
Proper development and function of white adipose tissue (WAT), which are regulated by multiple transcription factors and coregulators, are crucial for glucose homeostasis. WAT is also the main target of thiazolidinediones, which are thought to exert their insulin-sensitizing effects by promoting mitochondrial biogenesis in adipocytes. Besides being expressed in WAT, the role of the coactivator PGC-1β in this tissue has not been addressed. To study its function in WAT, we have generated mice that lack PGC-1β in adipose tissues. Gene expression profiling analysis of WAT reveals that PGC-1β regulates mitochondrial genes involved in oxidative metabolism. Furthermore, lack of PGC-1β prevents the induction of mitochondrial genes by rosiglitazone in WAT without affecting the capacity of thiazolidinediones to enhance insulin sensitivity. Our findings indicate that PGC-1β is important for basal and rosiglitazone-induced mitochondrial function in WAT, and that induction of mitochondrial oxidative capacity is not essential for the insulin-sensitizing effects of thiazolidinediones.